Sistem Monitoring pada Ruang Perpustakaan berbasis Internet of Things - William, Andre; Wagyana, Agus (Universitas Tarumanagara, 2023)
An Internet of Things (IoT) based library room monitoring system is an innovative solution that utilizes the latest technology to help monitor temperature, humidity, lighting levels and noise levels in library rooms. This system is designed to provide accurate and fast information to library managers. This system aims to make it easier for library managers to monitor library space. This system can be accessed via a mobile application, allowing library managers to monitor the library situation remotely. This system uses sensors connected to the internet to collect real-time data about the condition of the library room. These sensors are placed in the library reading room to monitor these parameters and send data to the database. The design of this monitoring system uses the ESP32 device as the main microcontroller which controls each sensor and internet connection and the ESP32CAM as the camera. The measurement of the relative error value is calculated based on the difference between the value from the actual tool and the value read by the sensor used. The value of the actual measuring instrument obtained will be used to calibrate each sensor so that the sensor results will be close to the value of the measurement results of the measuring instrument. Testing for each sensor is carried out 10 – 20 times to get more accurate test results. The relative error value for the DHT22 sensor temperature is 1.15% and the humidity is 5.12%. The relative error values for the BH1750 sensor when the lights are off and on are 2.84% and 2.10% respectively. The relative error values for the MAX 9814 sound sensor at a distance of 4 meters and 3 meters are 6.02% and 6.24% respectively. When noise occurs, the tool will respond in the form of a buzzer sound and take an image from the ESP32 CAM. The error values that appear on the BH 1750 and DHT 22 sensors are because the measuring instrument has the accuracy value of the measuring instrument, as well as the sensor accuracy, whereas in the MAX 9814 Sensor test it is due to deficiencies in the conversion of bit values to dB form and imperfect sensor calibration. ABSTRAK: Sistem monitoring ruangan perpustakaan berbasis Internet of Things (IoT) merupakan solusi inovatif yang memanfaatkan teknologi terkini untuk membantu memonitoring suhu, kelembapan, tingkat pencahayaan dan tingkat kebisingan pada ruang perpustakaan. Sistem ini dirancang untuk memberikan informasi yang akurat dan cepat kepada pengelola perpustakaan. Sistem ini bertujuan untuk mempermudah pengelola perpustakaan dalam memantau ruang perpustakaan. Sistem ini dapat diakses melalui aplikasi mobile, memungkinkan pengelola perpustakaan untuk memantau situasi perpustakaan dari jarak jauh. Sistem ini menggunakan sensor yang terhubung dengan internet untuk mengumpulkan data secara real-time tentang kondisi ruangan perpustakaan. Sensor-sensor ini ditempatkan di bagian ruangan baca perpustakaan untuk memantau parameter-parameter tersebut dan mengirimkan data ke database. Perancangan sistem monitoring ini menggunakan perangkat ESP32 sebagai mikrokontroler utama yang mengendalikan setiap sensor dan koneksi internet dan ESP32CAM sebagai kameranya. Pengukuran nilai eror relatif dihitung berdasarkan perbedaan antara nilai dari alat aktual yang ada dengan nilai yang dibaca oleh sensor yang digunakan. Nilai dari alat ukur aktual yang didapatkan akan digunakan untuk kalibrasi dari setiap sensor agar hasil sensor nantinya mendekati nilai dari hasil pengukuran alat ukur. Pengujian tiap sensor dilakukan 10 – 20 kali untuk mendapatkan hasil pengujian yang lebih akurat. Nilai eror relatif suhu sensor DHT22 adalah 1,15% dan kelembapannya 5,12%. Nilai eror relatif pada sensor BH1750 pada saat lampu mati dan menyala masing masing 2,84% dan 2,10%. Nilai eror relatif pada sensor suara MAX 9814 pada jarak 4 meter dan 3 meter masing masing 6,02% dan 6,24%. Saat terjadi kebisingan, alat akan memberikan respon berupa bunyi buzzer dan pengambilan gambar dari ESP32 CAM. Nilai eror yang muncul pada sensor BH 1750 dan DHT 22 karena alat ukur memiliki nilai akurasi dari alat ukur, serta akurasi sensor sedangkan pada pengujian Sensor MAX 9814 adalah karena kekurangan dalam konversi nilai bit ke bentuk dB serta kalibrasi sensor yang kurang sempurna.